2018
DOI: 10.1016/j.gastre.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic perspectives in non-alcoholic steatohepatitis

Abstract: Management of non-alcoholic steatohepatitis is focused on restitution of metabolic derangement, weight loss and drugs able to improve steatosis, ballooning and fibrosis. Life-style interventions based on Mediterranean diet and increasing physical activity are the first line therapy. In patients with unsuccessful life-style intervention several drugs are under development: agonist PPAR, agonist GLP-1R and agonist FXR together with drugs focussing on inflammation, ballooning, apoptosis and fibrosis. Bariatric su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…For treatment of NASH, the reversal of fibrosis is a key unmet need and data suggests > 10% body weight loss is necessary for an optimal result 9 , an objective difficult to reach and maintain by lifestyle modification alone. Bariatric surgery remains the most effective route to achieve longer-term, definitive weight loss and reversal of obesity-driven comorbidities such as NAFLD/NASH 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…For treatment of NASH, the reversal of fibrosis is a key unmet need and data suggests > 10% body weight loss is necessary for an optimal result 9 , an objective difficult to reach and maintain by lifestyle modification alone. Bariatric surgery remains the most effective route to achieve longer-term, definitive weight loss and reversal of obesity-driven comorbidities such as NAFLD/NASH 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have demonstrated that healthy changes in dietary habits can promote a clinically meaningful regression of disease status [ 19 ]. For this reason, life-style interventions based on nutritional changes is considered the first line therapy in preventing or ameliorating MAFLD [ 20 ]. In this way, plant peptide such as those from soy have been shown not only to lower the MAFLD status in animals [ 21 ] and humans [ 18 ] but also to be able to decrease the main obesity risk factors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We are now in a race to identify the first drug able to prevent NAFLD or reverse the disease course in patients at more advanced stages. 3 Clinical trials for NAFLD pose many challenges. 4 On the one hand, some problems relate to recruitment.…”
Section: Current Challenges In Nafld Clinical Trialsmentioning
confidence: 99%
“…11 In this review, we analyse the existing literature on the impact of metabolic comorbidities and lifestyle on treatment response, how this is reported in the different published clinical trials, and how we can use this information to optimise stratification. 1 Hospital Universitario Virgen del Rocío, Sevilla, Spain; 2 SeLiver Group, Instituto de Biomedicina de Sevilla, Sevilla, Spain; 3 CIBERehd, Spain…”
Section: Current Challenges In Nafld Clinical Trialsmentioning
confidence: 99%